2020
DOI: 10.3389/fphys.2020.00172
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 Receptor α Chain Protects the Kidney Against Tubule-Interstitial Injury Induced by Albumin Overload

Abstract: Increasing evidence has highlighted the role of tubule-interstitial injury (TII) as a vital step in the pathogenesis of acute kidney injury (AKI). Incomplete repair of TII during AKI could lead to the development of chronic kidney disease. Changes in albumin endocytosis in proximal tubule epithelial cells (PTECs) is linked to the development of TII. In this context, interleukin (IL)-4 has been shown to be an important factor in modulating recovery of TII. We have studied the possible role of IL-4 in TII induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…In our previous data, BSA challenge leads to inflammatory cytokine release and immune dysfunction in the cortical and medullary areas, which aggravates tubule damage and interstitial inflammation triggered by sepsis [11]. In addition, alterations in the albumin reabsorption machinery and changes in collagen deposition occur during this process [24]. We report here that ATRvD1 treatment reduced proteinuria excretion, UPC ratio, glomerular cell number and ECM deposition.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In our previous data, BSA challenge leads to inflammatory cytokine release and immune dysfunction in the cortical and medullary areas, which aggravates tubule damage and interstitial inflammation triggered by sepsis [11]. In addition, alterations in the albumin reabsorption machinery and changes in collagen deposition occur during this process [24]. We report here that ATRvD1 treatment reduced proteinuria excretion, UPC ratio, glomerular cell number and ECM deposition.…”
Section: Discussionmentioning
confidence: 48%
“…TGF activates pro-fibrotic pathways, leading to ECM deposition. BSA overload induces high TGF levels, which correlates with the renal damage [20,24]. Moreover, COL3 and COL4 are normally expressed in the kidney and are increased during fibrosis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that these changes are accompanied by tubular dilation, glomerular remodeling. and collagen deposition in addition to an increase in IL-6, TNF-α, and TGF-β [ 36 , 37 , 38 ]. On the other hand, randomized studies performed with critically ill patients have shown that the albumin overload (“hyper-oncotic albumin”) used to stabilize hemodynamics does not generate nephrotoxic effects during the hospital stay period [ 39 ].…”
Section: Albumin and Its Relationship With Kidney Diseasementioning
confidence: 99%
“…One of the main causes of the development of TII is albumin overload in the proximal tubule (PT) caused by increased filtration at the glomerular membrane [ 5 , 6 , 7 ]. This process induces functional changes in PT epithelial cells (PTECs), leading to the development of a pro-inflammatory and pro-fibrotic phenotype [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. In this context, identification of treatments for TII could represent a forward step to halt the progression of renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigated the effect of EOCZ treatment in healthy Swiss mice and in a subclinical acute kidney injury (subAKI) animal model which developed TII induced by PT albumin overload [ 8 , 9 , 10 , 11 , 12 , 13 ]. Swiss mice were treated with 300 mg/kg/day EOCZ, a dose at the upper range of those used pharmacologically in previous studies [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%